ANALISIS KEPUASAN TERHADAP KUALITAS PELAYANAN PADA BENGKEL MOBIL NEGRO PALEMBANG SUMATERA SELATAN - Mujito Mujito; Benny Osta Nababan; Muhlis Muhlis; Rani Destriana (Institut Teknologi dan Bisnis Dewantara, 2023)
This research aims to determine the level of service performance and consumer expectations as well as service indicators that are the company's priorities. This type of research is quantitative descriptive research. The number of samples is 100 samples with data analysis including service quality analysis, CSI analysis and IPA analysis (Importance Performance Analysis). The research results show that: (1) Based on the results of the gap analysis, it can be seen that almost all indicators have negative values. There is 1 indicator that has a positive value, namely indicator number 7, namely: